Developing group support systems for Indonesian culture at the pre-meeting stage of strategy formulation: A proposal and some initial requirements - Abdat, Sjarif; Pervan, Graham (The School of Information Management & Systems, Monash University, 1999)
Research about Group Support Systems and the design of these group support technologies mainly uses western culture as a point of reference. While the research reveals promising results on the effectiveness of these technologies, the research results and the technologies themselves may be less effective when applied directly to different cultures or cross-cultural situations. This paper aims to explore design requirements for technological support for groups engaged in strategy formulation in Indonesia, a national culture which has relatively high power distance, low individualism, and weak uncertainty avoidance (Hofstede, 1980),and high context (Hall and Hall, 1990). We suggest analysing a typical group meeting activity (strategy formulation) in Indonesia at the pre-meeting stage and propose a programme of research to design and develop supporting technologies in this cultural environment, and then evaluate them in the field. Some results from the early stage of the requirement determination including cultural issues are presented.